2009
DOI: 10.1007/s10562-009-0165-y
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Cu(I) Species for Photocatalytic Hydrogen Generation Over CuO x /TiO2

Abstract: The fabrication of different CuO x species (Cu(0), Cu(I) and Cu(II) species) over TiO 2 has been accomplished and their roles in photoinduced hydrogen generation have been investigated. The results indicate that the positive charge in CuO x center affect photo-induced charge transfer significantly. Cu(I) species seems promote photocurrent generation while the Cu(II) species inhibits the photocurrent generation. Photoactivity order follows the similar sequence. Lower temperature calcination helps the formation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
62
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(65 citation statements)
references
References 43 publications
3
62
0
Order By: Relevance
“…Cu x O-TiO 2 (x = 1, 2) nanocomposites were tested for ethanol PR [180,181]. The best performance was achieved with 1 wt% metal loading, due to the main presence of Cu(I) ions, active sites for the transfer of photogenerated electrons, whereas Cu(II) species seem to promote electron-hole recombination.…”
Section: Photoreforming Of Alcoholsmentioning
confidence: 99%
“…Cu x O-TiO 2 (x = 1, 2) nanocomposites were tested for ethanol PR [180,181]. The best performance was achieved with 1 wt% metal loading, due to the main presence of Cu(I) ions, active sites for the transfer of photogenerated electrons, whereas Cu(II) species seem to promote electron-hole recombination.…”
Section: Photoreforming Of Alcoholsmentioning
confidence: 99%
“…Due to the low cost and availability, copper would be a better choice to modify TiO 2 . Many researchers had reported copper modified TiO 2 catalysts for enhanced photocatalytic activities and also photocatalytic reduction of CO 2 [15][16][17][18][19]. Liu et al have synthesized copper-loaded titania photocatalysts in one pot reaction and observed enhancement in CO 2 reduction to CO than with pure TiO 2 [20].…”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19][20][21][22][23][24] Among them, Cu 2+ ion and CuO have attracted much interest as a promising surface modifier. [25][26][27][28][29][30][31][32] Interestingly, Irie et al have shown that Cu 2+ -grafted TiO 2 (Cu 2+ /TiO 2 ) prepared by the impregnation method has oxidation ability sufficient for completely decomposing 2-propanol under visible-light irradiation. 28 Even if visible-light activity appears, it is usually much smaller than UV-light activity, and thus, the compatibility of high visible and UVlight activities is important from a viewpoint of effective sunlight use.…”
Section: Introductionmentioning
confidence: 99%